Situating Human Rights Violation Narratives in the Tragedy of the FPI Militia Shooting Incident in the Film 'Kilometer 50’ - Dwyangghara, Muhammad Arief; Maryani, Eni; Mirawati, Ira (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2019)
The documentary film "Kilometer 50" directed by Andibachtiar Yusuf tells the tragedy behind the shooting case of the Islamic Defenders Front Laskar on the Jakarta-Cikampek KM 50 Toll Road. This documentary film was raised from the findings obtained by Tempo journalists through several sources and witnesses in the incident. This research discusses the narrative structure of the documentary film "Kilometer 50" to find out in depth how the alleged human rights violations were committed by the police in the tragedy. The method used in this research is qualitative with Tzvetan Todorov's narrative analysis approach. Data collection techniques are done by analyzing documentation, observation, and literature study. The purpose of this research is to find out how the narrative message of human rights violations is contained in the documentary film "Kilometer 50" based on narrative analysis using the Tzvetan Todorov model which considers that the narrative consists of verb aspects.  The verb aspects include mode category, time category, point of view category and narration category. The results showed that the plot in the documentary film "Kilometer 50" there are 17 messages of violation found based on the categories in the verb aspect of the whole story. Among them, in the mode category, there are 5 scenes with 2 direct style scenes and 3 scenes with indirect style. Then in the time category, there is 1 scene in the initial flow and 4 scenes in the final flow. Then in the point of view category there are 2 scenes. In the narrative category, there are 5 scenes.